Early Warning: Educational Innovation to Minimize the Risk of School Dropouts in the Evening High Schoo of Pococí - Jiménez-Castro, Maynor (2021)
In this article, an educational innovation for the reduction of school dropout is described through a strategy called Early Warning, which consists of registering a series of aspects that the students show when they are at risk of dropping out from the educational system. The strategy is part of the Yo me apunto program implemented by the Costa Rican Ministry of Public Education, but has been adapted by the Pococí Adult Night High School (CNP) in order to use mobile technologies and the Google forms tool to make reports mainly of absenteeism by the teachers, while the group of school counselors follow each case up. This mechanism has allowed to identify the main risk factors that students present before leaving school, which makes it possible to provide prompt and timely attention to the cases and proper decision-making by institutional authorities. This article describes the experience obtained in the CNP, where the exclusion rates are very high, and the results of applying this strategy show a significant improvement in the monitoring and prevention of the risks of high school dropouts.